Management of Diarrhoeal Dehydration in Childhood: A Review for Clinicians in Developing Countries - Anigilaje, Emmanuel Ademola (Frontiers in Pediatrics, 2018)
The survival of a child with severe volume depletion at the emergency department depends on the competency of the first responder to recognize, and promptly treat hypovolemic shock. Although the basic principles on fluid and electrolytes therapy have been investigated for decades, the topic remains a challenge, as consensus on clinical management protocol is difficult to reach, and more adverse events are reported from fluid administration than for any other drug. While the old principles proposed by Holliday and Segar, and Finberg have stood the test of time, recent systematic reviews and meta-analysis have highlighted the risk of hyponatraemia, and hyponatraemic encephalopathy in some children treated with hypotonic fluids. In the midst of conflicting literature on fluid and electrolytes therapy, it would appear that isotonic fluids are best suitable for the correction of hypotonic, isonatraemic and hypernatraemic dehydration. Although oral rehydration therapy is adequate to correct mild to moderate isonatraemic dehydration, parenteral fluid therapy is safer for the child with severe dehydration and those with changes in serum sodium. The article reviews the pathophysiology of water and sodium metabolism and, it uses the clinical case examples to illustrate the bed-side approach to the management of three different types of dehydration using a pre-mixed isotonic fluid solution (with 20 or 40 mmol/L of potassium chloride added depending on the absence or presence of hypokalaemia respectively). When 3% sodium chloride is unavailable to treat hyponatraemic encephalopathy, 0.9% sodium chloride becomes inevitable, albeit, a closer monitoring of serum sodium is required. The importance of a keen and regular clinical and laboratory monitoring of a child being rehydrated is emphasized. The article would be valuable to clinicians in less-developed countries, who must use pre-mixed fluids, and who often cannot get some suitable rehydrating solutions.